2012
DOI: 10.1007/s00429-012-0427-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered diffusion tensor imaging measurements in aged transgenic Huntington disease rats

Abstract: Rodent models of Huntington disease (HD) are valuable tools for investigating HD pathophysiology and evaluating new therapeutic approaches. Non-invasive characterization of HD-related phenotype changes is important for monitoring progression of pathological processes and possible effects of interventions. The first transgenic rat model for HD exhibits progressive late-onset affective, cognitive, and motor impairments, as well as neuropathological features reflecting observations from HD patients. In this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
(159 reference statements)
1
13
0
Order By: Relevance
“…Compared with the already existing fragment tgHD rats BACHD rats show an earlier onset and a faster progression of motor deficits without the need to breed for homozygosity as heterozygous tgHD rats show only subtle deficits . Recently, a milder phenotype in tgHD rats as originally described has been reported (Casteels et al, 2011;Antonsen et al, 2012;Blockx et al, 2012). Also, while striatal atrophy was found in some groups of old tgHD rats (von Hörsten et al, 2003;, other studies revealed little or no evidence for atrophy (Winkler et al, 2006;Bode et al, 2008;Blockx et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Compared with the already existing fragment tgHD rats BACHD rats show an earlier onset and a faster progression of motor deficits without the need to breed for homozygosity as heterozygous tgHD rats show only subtle deficits . Recently, a milder phenotype in tgHD rats as originally described has been reported (Casteels et al, 2011;Antonsen et al, 2012;Blockx et al, 2012). Also, while striatal atrophy was found in some groups of old tgHD rats (von Hörsten et al, 2003;, other studies revealed little or no evidence for atrophy (Winkler et al, 2006;Bode et al, 2008;Blockx et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Despite the structural changes in HD tissue, we have not seen a significant change in the diffusion anisotropy among matched axes between HD and WT mice. In contrast, other studies report an increased FA in the GP (Douaud et al, 2009;Antonsen et al, 2013). Douaud and colleagues (2009) proposed that increased FA in striatal gray matter structures is due to the loss of efferent fibers, which in turn leads to increased coherence.…”
Section: Discussionmentioning
confidence: 94%
“…Investigations that go beyond simple structural measures, as used here, should be performed. Ideally, MR spectroscopy and diffusion MRI complement T 2 -weighted structural scans, as these can potentially provide more specific markers of tissue changes in the striatum and cortex [68, 69]. It is important to note though that even in transgenic animals these investigations are not trivial in terms of logistics and costs, but could provide robustly quantifiable and validated biomarkers to define the various stages of the condition.…”
Section: Discussionmentioning
confidence: 99%